Understanding complex military operations : a case study approach - Franke, Volker, 1963-; Guttieri, Karen, 1964-; Civic, Melanne A. (London : Routledge, 2014)
'This volume provides materials for active learning about peacebuilding and conflict management in the context of complex stability operations, using a comparative case study methodology.Complex operations are collaborative and coordinated military and civilian agency activities executed to restore stability to fragile states, and to aid the transition to democratic governance operating under the rule of law. All actors engaged in complex stability operations need to understand the requirements for effective civil-military and interagency coordination from different perspectives (military, civilian, diplomacy, development, allied, local). Effective conflict prevention and transformation requires greater coherence between security, governance and development policies along with enhanced coordination among governmental agencies and with local, regional and international partners (as in'smart power' -- pursuing the right tools for each operational context). Conflict management strategies and whole-of-government approaches are closely connected. In fragile states and post-conflict societies, security, governance and development are challenges that need to be addressed simultaneously and in coordinated fashion.As a consequence of the multitude of threats, actors and tasks in such operations, decisions will cut across a wide range of social, political and cultural domestic and global issues and demand cognitive flexibility, adaptability and the ability to make decisions'on the fly'. The need for strategic and operational decision-making at every turn requires that the actors -- military and civilian alike -- acquire the mental agility, interpersonal maturity and cross-cultural savvy. These competencies need to be ingrained into the readily available skill sets for military and civilian leaders so they become second-nature to their decision-making. The case studies in this volume integrate research -- theoretical and empirical -- that effectively identifies patterns of conflict, characteristics of complex operations and conditions for their effective conduct. It thereby provides educational materials for introducing and actively engaging students and practitioners in the intricacies of contemporary national security decision-making. This volume will be of much interest to students of conflict prevention, transitional justice, peacebuilding, security studies and professionals conducting field-based operations in potentially hazardous environments.'--
Includes bibliographical references and index.
Keywords: Integrated operations (Military science) -- Case studies; Armed Forces -- Stability operations -- Case studies; Nation-building -- Case studies; Peace-building -- Case studies; Interagency coordination -- United States -- Case studies; Post-conflict reconstruction -- Case studies; Conflict management -- Case studies